Proceedings of the 30th International Technical Meeting of the Satellite Division of the Institute of Navigation (ION GNSS+ 201 2017
DOI: 10.33012/2017.15174
|View full text |Cite
|
Sign up to set email alerts
|

Multi-GNSS Constellation Anomaly Detection and Performance Monitoring

Abstract: Prior to joining the lab in fall 2015 as a Ph.D. candidate, Kaz worked for Booz Allen Hamilton on the GPS Systems Engineering and Integration group doing Modeling and Simulation of the next generation GPS Control Segment and software-defined receiver work looking at the GPS III waveform. His interests are in GNSS modernization and integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…SIS anomalies (i.e., faults) are mainly caused by incorrect navigation data, orbital maneuvers, abnormal orbital disturbances, clock jumps, clock drifts, and other unusual events (Gunning et al., 2018). SIS faults can potentially lead to large navigation errors and constitute the major threats to navigation safety in aviation applications.…”
Section: Anomalies: Detection and Probability Determinationmentioning
confidence: 99%
“…SIS anomalies (i.e., faults) are mainly caused by incorrect navigation data, orbital maneuvers, abnormal orbital disturbances, clock jumps, clock drifts, and other unusual events (Gunning et al., 2018). SIS faults can potentially lead to large navigation errors and constitute the major threats to navigation safety in aviation applications.…”
Section: Anomalies: Detection and Probability Determinationmentioning
confidence: 99%
“…The APE describes the average of the UPE for all users, which has been widely used for positioning service performance standard [19]. The MPE, also known as the worst-case of IURE, is often used as the test statistic for fault detection because the most vulnerable user should be protected with the allowable integrity risk [20][21][22][23]. Therefore, the MPE derived from the IURE of the equivalent phase error can be constructed as the test statistic to detect the faults in the correction products.…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers [1] have described methods of estimating these parameters over long periods and rely heavily on the availability of IGS precise products. However, it has been shown that such precise products are not always available, even during periods where faults have been observed [2] [3]. The goal of IGS analysis centers is accuracy, not necessarily 100% availability, so when anomalous behavior by the satellite is detected, an estimate may not be output.…”
Section: Introductionmentioning
confidence: 99%